STRENGTHENING FINANCIAL SYSTEM STABILITY THROUGH ENHANCING INTERMEDIARY FUNCTION AND EFFICIENCY OF BANK PEMBANGUNAN DAERAH (REGIONAL DEVELOPMENT BANK) - Endri, Endri (Journal of Indonesian Economy and Business, 2009)
This paper analyzes the function of the regional development banks (BPD) as an intermediary institution using the loan to deposit ratio (LDR) and Bank Indonesia Certificate to deposit ratio (SDR) and efficiency performance with data envelopment analysis (DEA) approach with data during 2006-2007 covering 26 BPD in Indonesia. The result of study indicates that the regional development banks do not play its optimal role as the intermediary institution and efficiency performance do not achieve the level of maximum 100 persen. For getting the optimal function of banking intermediary and promoting better efficiencies, BPD needs to design some steps of the grand strategy that can be developed in the future, that is: the limitation of funds placed by BPD in Bank Indonesia Certificate notes, inter BPD networking, focus on market segmentation, diversification source of funds, and creating local credit guaranting institutions.Keywords: bank efficiency, bank intermediary, loan to deposit ratio (LDR), SBI to deposit ratio (SDR), data envelopment analysis (DEA)